Cloning of sucrose isomerase encoding gene from Klebsiella singaporensis ISB-36 and its expression in Pichia pastoris - Bach, Cao Xuan; Thi Kim Anh, Dang; Thanh Thuy, Nguyen; Tu Anh, Truong; Thi Dieu Linh, Nguyen; Nguyen Thanh, Vu (Vietnam Journal of Biotechnology, 2020)
Given potential health benefits including low glycemic index, tooth friendly, suitable to infants, elderly and diabetic patients, isomaltulose was considered as a promising alternative sweetener to sucrose. Due to the presence of liposaccharide endotoxin in Serratia plymuthica CBS 574.44, a Gram-negative bacterium, and minute amount of formaldehyde carried over, purification of isomaltulose requires rigorous controls in industry. To reduce the cost associated with product purification, here we propose the use of recombinant enzyme in isomaltulose production. The mature gene coding for sucrose isomerase synthase (K.SI36.PalI) from Klebsiella singarporensis ISB 36, which isolated from woodborer in Vietnam, was expressed in Pichia pastoris X33. The nucleotide sequence of K.SI36.PalI gene was similar to AY040843.1 of Klebsiella sp. LX3 except one nucleotide C1025 in AY040843.1 replaced by T1025 in K.SI36.PalI. This leads to single amino acid difference in deduced protein sequence (from 342Ser to 342Phe). Furthermore, the addition of two amino acids (Glu and Phe) was observed at N-terminus. The calculated molecular weight of sucrose isomerase from K.SI36.PalI was 67.46 kDa and the pI was 6.55. There was one potential glycosylation site at 466Asn. The maximum sucrose isomerase activity in the culture broth reached 36,6 U.mL-1in 1 L shake-flask. The purified recombinant enzyme was most active at 40°C and pH 7.0. At the optimum condition, within 6 hours, the enzyme converted 94% of sucrose in a 40% sucrose solution into isomaltulose. This was the first study on the expression of sucrose isomerase synthase gene in P. pastoris, and the results showed the efficient conversion of sucrose isomerase recombinant.